2021
DOI: 10.3389/fpubh.2021.691880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiofrequency Electromagnetic Radiation on Neurotransmitters in the Brain

Abstract: With the rapid development of electronic information in the past 30 years, technical achievements based on electromagnetism have been widely used in various fields pertaining to human production and life. Consequently, electromagnetic radiation (EMR) has become a substantial new pollution source in modern civilization. The biological effects of EMR have attracted considerable attention worldwide. The possible interaction of EMR with human organs, especially the brain, is currently where the most attention is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 117 publications
0
54
0
2
Order By: Relevance
“…The brain is recognized as being one of the target organs that are sensitive to EMR. Numerous studies have shown that EMR can cause cognitive impairment in the brain under certain conditions (Shahin et al, 2018;Narayanan et al, 2019;Gökçek-Saraç et al, 2021;Hu et al, 2021;Tan et al, 2021). There are few studies regarding the effects of EMPs on behavior and nerves, and further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The brain is recognized as being one of the target organs that are sensitive to EMR. Numerous studies have shown that EMR can cause cognitive impairment in the brain under certain conditions (Shahin et al, 2018;Narayanan et al, 2019;Gökçek-Saraç et al, 2021;Hu et al, 2021;Tan et al, 2021). There are few studies regarding the effects of EMPs on behavior and nerves, and further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
“…The brain is considered to be sensitive to EMR, as many studies have reported the damaging effects of EMR on the brain (Shahin et al, 2018;Narayanan et al, 2019;Gökçek-Saraç et al, 2021;Hu et al, 2021;Tan et al, 2021). Learning and memory are the basis of brain cognitive function.…”
Section: Emps Impaired the Spatial Learning And Memory Ability In Micementioning
confidence: 99%
See 1 more Smart Citation
“…This not only has an impact on the performance of sensors but can also cause damage to human health through electromagnetic radiation. Longer exposure to electromagnetic radiation can result in adverse reactions in the central nervous system which can lead to cognitive impairment and pose a higher risk of brain tumours [178]. There are some beneficial effects of short-term exposure to microwave radiation, it can improve cognitive functions, short-term memory loss and attention disorder [179].…”
Section: G Mitigation Of Near-body Effects On Portable Sensor Systems...mentioning
confidence: 99%
“…The precise mechanisms by which microwaves affect the biological system remain largely unknown due to differing equipment and inadequate techniques, bringing uncertainty into the available data. Despite this, many hypotheses have been generated to describe the possible mechanisms of the biological effects of microwaves [ 34 ]. An overview of these mechanisms is shown in Figure 2 , whereas the most common mechanism is shown in Figure 3 .…”
Section: Introductionmentioning
confidence: 99%